From DNA to biomass: opportunities and challenges in species quantification of bulk fisheries products. (18th August 2020) - Hansen, Brian Klitgaard; Farrant, Gregory Kevin; Ogden, Rob; Humble, Emily; Ólafsdóttir, Guðbjörg; Bekkevold, Dorte; Knudsen, Steen Wilhelm; Møller, Peter Rask; Nielsen, Einar Eg
Abstract: Fisheries enforcement relies on visual catch identification and quantification at sea or when landed. Silage (fish dissolved in acid) and fish blocks (block frozen fish) are promising methods for on-board processing and storage of low-value catches. We examined the use of non-destructive sampling and two DNA-based methods, quantitative PCR (qPCR) and metabarcoding, to assess species composition and relative abundance in industrial grade experimental silage and fish blocks. We demonstrate the ability to identify and quantify DNA from fish species in both products. qPCR analysis of small silage samples collected over 21 days detected all target control species. DNA from one species (Atlantic wolffish) was consistently overrepresented while, for three species of gadoids (Atlantic cod, haddock and whiting), the DNA content matched input tissue proportions with high accuracy. qPCR and metabarcoding of fish blocks, sampled as run-off water and exterior swabs, provided consistent species detection, with the highest variance observed in quantification from swab samples. Our analysis shows that DNA-based methods have significant potential as a tool for species identification and quantification of complex on-board-processed seafood products and are readily applicable to taxonomically and morphologically similar fish. There is, however, a need for establishing DNA/weight calibration factors for primary fisheries species.